2000
DOI: 10.15760/etd.5385
|View full text |Cite
|
Sign up to set email alerts
|

Staying Within the Margins: The Educational Stories of First-Generation, Low-Income College Students

Abstract: This research addressed educational persistence among first-generation, lowincome college students. The educational paths of 22 first-generation, low-income undergraduate students attending a large, urban university in the Northwest region of the United States were examined through a narrative framework. Half of the participants had persisted from year one to year two, and the other half left the university after their first year. Analytic procedures consisted of thematic qualitative coding, an analysis of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…One study found that first-generation and lowincome college students felt disempowered and marginalized by their university, finding such students felt like outsiders because of their cultures and experiences which were so vastly different from that of the academic culture, also many felt the faculty looked down upon them, were not available, were not academically supportive, and had extreme difficulty in connecting with other students to form a community on campus (Lobo, 2001). Cole (2008) found many first-generation college students who left did so for reasons that were not necessarily academic or financial and found many left due to a perceived lack of support and encouragement from others in regard to their educational pursuits, did not feel a connection with the university, did not embrace the notion they were doing something worthwhile, and did not have overall positive feelings about their environment. It is important for institutions to establish programs aimed specifically at first-generation and low-income students.…”
Section: Institutional Approaches and Obstaclesmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that first-generation and lowincome college students felt disempowered and marginalized by their university, finding such students felt like outsiders because of their cultures and experiences which were so vastly different from that of the academic culture, also many felt the faculty looked down upon them, were not available, were not academically supportive, and had extreme difficulty in connecting with other students to form a community on campus (Lobo, 2001). Cole (2008) found many first-generation college students who left did so for reasons that were not necessarily academic or financial and found many left due to a perceived lack of support and encouragement from others in regard to their educational pursuits, did not feel a connection with the university, did not embrace the notion they were doing something worthwhile, and did not have overall positive feelings about their environment. It is important for institutions to establish programs aimed specifically at first-generation and low-income students.…”
Section: Institutional Approaches and Obstaclesmentioning
confidence: 99%
“…Also, qualitative studies are highly beneficial in a number of studies in obtaining a deeper understanding of the struggles, challenges, and experiences of first-generation, low-income college students (Beegle, 2000;Bergh, 2008;Lask, 2008;Cole, 2008;Martin, 2012;London, 1989;Bukoski, 2012). The study by Beegle (2000) relates particularly well to the proposed study here.…”
Section: Qualitative Approachmentioning
confidence: 99%
See 1 more Smart Citation